Horizons architecture with virtual reality for complexity: Mixed methods - Maria Soledad Ramirez Montoya; Sandra Martinez Perez; Laura Patricia Zepeda Orantes (OmniaScience, 2024)
In the field of complexity, new methodologies emerge, such as horizon architecture, which help to focus solutions that can be integrated to foster innovation in university education. Technologies are also opening up opportunities for training, such as virtual and augmented reality. This article aims to answer the question: What innovations do postgraduate students perceive in environments using horizons architecture to integrate virtual reality? In this project's training experience for students, the horizons architecture strategy was implemented with virtual reality resources and emerging technologies. Mixed method with three instruments (two semi-structured questionnaires and one Likert scale) were applied to 99 postgraduate students in Humanities and Education. Virtual and augmented reality supported the distance education modalities and project presentations. The findings account for: (a) open and systemic innovation, (b) creation of new products and services, (c) the potential of horizons architecture strategy, (d) motivation boosted by virtual and augmented reality, and (e) critical aspects of integrating virtual and augmented reality (technical and academic). This study may be valuable to teachers, entrepreneurs, and decision-makers interested in innovative educational environments and technologies, especially those in graduate education.